FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PENYAKIT TUBERCULOSIS(TBC) DI WILAYAH KERJA PUSKESMAS LASALIMU KABUPATEN BUTON - Dahmar Dahmar; Wa Ode Azfari Azis; Fitriani Fitriani; Waode defi astiani Defi (Kampurui Jurnal Kesehatan Masyarakat, 2022)
Tuberculosis is an infectious disease that can cause health problems and is also one of the top 10 causes of death in the world due to infectious diseases (ranked above HIV/AIDS). The purpose of the study was to determine the factors associated with the incidence of tuberculosis (TB) in the Lasalimu Public Health Center, Buton Regency. The type of research is analytic observational method using a cross sectional  approach, namely to determine the relationship of the independent variable (smoking and ventilation habits) with the dependent variable (Tuberculosis incidence). The population in this study was the entire community in the Lasalimu Health Center Working Area, Buton Regency as many as 6,515 people, the sample amounted to 98 people and the sampling method used was simple random sampling. The data analysis used was univariate analysis and bivariate analysis at 95% confidence level ( = 0.05). The conclusion obtained shows that there is a relationship between smoking habits (ρ = 0.002 < 0.05) and ventilation (ρ 0.000 < 0.05) with the incidence of tuberculosis (TB) in the Lasalimu Public Health Center, Buton Regency. Suggestions for respondents/community if they feel symptoms of Tuberculosis such as coughing up phlegm for more than 2 weeks to immediately come to the puskesmas for examination in the laboratory and are expected to stop smoking in order to suppress the occurrence of tuberculosis cases. about efforts to prevent tuberculosis as well as providing